Legend of the guardians The owls of Ga'Hoole - Cornish, Abbie, 1982-; Margolyes, Miriam; Mirren, Helen; Neill, Sam.; Rush, Geoffrey, 1951-; Sturgess, Jim.; Weaving, Hugo, 1960-; Orloff, John.; Stern, Emil.; Nalbandian, Zareh; Snyder, Zack, 1966-; Lasky, Kathryn; et al. (Burbank, Calif. : Warner Home Video, 2010)
Young owl Soren marvels at his father's epic stories of the Guardians of Ga'Hoole, mythic winged warriors who fought a great battle to save all owlkind from the evil Pure Ones. When he and brother Kludd fall from their treetop home and into the talons of the Pure Ones, it's up to Soren to make a daring escape with the help of other brave owls.
Widescreen.
Based on the novel Guardians of Ga'Hoole by Kathryn Lasky.
DVD release of the 2010 motion picture.
Special features: True guardians of the Earth featurette; new Looney tunes cartoon Fur of flying.
Edited by David Burrows ; music by David Hirschfelder.
Voices: Abbie Cornish, Miriam Margolyes, Helen Mirren, Sam Neill, Geoffrey Rush, Jim Sturgess, Hugo Weaving.
Keywords: Owls -- Drama; Good and evil -- Drama; Children's films; Fantasy films; Animated films; Feature films; Film adaptations; Video recordings for the hearing impaired